Characteristics of Museum’s Website In Jakarta As A Publication Site - Erna Mariana Susilowardhani; Rachel Dyah Wiastuti (Atma Jaya Indonesia Catholic University, Jakarta, 2014)
Nowadays, a website is considered primarily as a means of communication and categorized as one of many publications. Majority of prospective tourism visitors start their research on the internet. Therefore, having a website on the internet is a very important tool for any tourism business, including museums that would obviously give benefit for both the visitors and the museum itself. A well designed and maintained website will represent and evolve to being a museum’s image worth as one of tourism attractions. The purpose of this paper is to analyze a museum’s website and to examine its characteristics. This paper used a qualitative-explorative research. The Jakarta Tourism Board website was used as main reference to obtain which museum that was selected. Secondary data were from 10 official museums’ website observations in Jakarta. The results provide detail analysis about museum’s website through in-depth description referring to each particular characteristic; history, visitor information, collection, media press release, education, exhibition, research and social media. Each provides adequate information for visitors. This study contributes to the understanding of museum management to better acknowledge their website. The result of this study also provides strategic directions to enhance museum’s website performance expected to be in line with visitors’ experience.